Faculty diversity matters: a scoping review of student perspectives in North America. (2nd October 2022) - Sandhu, Harman Singh; Chen, Ruth; Wong, Anne
ABSTRACT: Faculty diversity and affirmative action in institutes of higher education (IHEs) have been discussed widely for many decades. In the literature, less is known about student viewpoints on faculty and administration diversity. We conducted a scoping review of the literature to examine student perspectives of faculty and administration diversity within IHEs in North America. Multiple databases were searched and 33 articles were included in the results. Our synthesis revealed that students, across disciplines and levels, perceived a lack of diversity among faculty and administration. Students recognised that diversity in the classroom, opportunities for mentorship, and experiences with discrimination had a significant impact on their learning and growth. Lastly, student perspectives and interactions with diverse faculty and administration varied based on students' own identities. This scoping review provides insights into how faculty and administration diversity directly impacts the student experience at IHEs. We discuss implications for future research and policy.